HUNGERS: FROM FOOD AND LACK OF IT TO HUNGER FOR PROFITS - Gomes Júnior, Newton (2023)
The essay presented refers to the XIV International Congress on Human Rights promoted by the School of Judges of the State of Tocantins, in the city of Palmas between October 19 and 21, 2022. The central argument refers to the idea that the scandal represented by hunger numbers, far from being a scourge, is the most evident expression of a society submitted to the needs of capital in detriment to the adequate satisfaction of basic human needs. The considerations developed from the central argument go through the dimensions of the State's duty in guaranteeing the conditions of citizenship, and focus on the manipulation of the social imaginary as to the meanings of the idea of food and food insecurity. Through dialogues with reference authors on the theme of hunger, food and food security, the conclusion is based that attributes to the needs of capital the main determinant of the current condition of food insecurity.